Climate induced human demographic and cultural change in northern Europe during the mid-Holocene. Issue 1 (December 2017) - Warden, L.; Moros, M.; Neumann, T.; Shennan, S.; Timpson, A.; Manning, K.; Sollai, M.; Wacker, L.; Perner, K.; Häusler, K.; Leipe, T.; Zillén, L.; et al.
Abstract The transition from hunter-gatherer-fisher groups to agrarian societies is arguably the most significant change in human prehistory. In the European plain there is evidence for fully developed agrarian societies by 7, 500 cal. yr BP, yet a well-established agrarian society does not appear in the north until 6, 000 cal. yr BP for unknown reasons. Here we show a sudden increase in summer temperature at 6, 000 cal. yr BP in northern Europe using a well-dated, high resolution record of sea surface temperature (SST) from the Baltic Sea. This temperature rise resulted in hypoxic conditions across the entire Baltic sea as revealed by multiple sedimentary records and supported by marine ecosystem modeling. Comparison with summed probability distributions of radiocarbon dates from archaeological sites indicate that this temperature rise coincided with both the introduction of farming, and a dramatic population increase. The evidence supports the hypothesis that the boundary of farming rapidly extended north at 6, 000 cal. yr BP because terrestrial conditions in a previously marginal region improved.